On New Closed Sets in Grill Topological Spaces (Global Journal of Science Frontier Research, 2023)
In the present work, the main intention is to introduce new type of closed sets namelyGg**-closed sets in Grill Topological spaces and study some of their properties.
Keywords: topological space; grill; operatorφ; g-closed set; Gg-closed set; Gg*-closed set; Gg**-closed set